A review of spectral energy distribution modeling at high-redshift. Issue Volume 15:Issue S352(2019) (June 2019) - Charlot, Stéphane
Abstract: I will review recent developments in the modeling of high-redshift galaxy spectra, focusing in particular on the rest-frame ultraviolet and optical emission from young stellar populations and the interstellar medium.